Navigating Technostress in primary schools: a study on teacher experiences, school support, and health - Wang, Zhuo; Zhang, Li; Wang, Xinghua; Liu, Lei; Lv, Cixian (Frontiers in Psychology, 2023)
Navigating Technostr ess in pr imar y schools: A study on teacher exper iences, school suppor t, and health Abstr act: The COVID-19 pandemic has led to a global shift towards online education, which has increased the use of technology for communication, management, and remote teaching. This study aimed to investigate how primary school teachers in China used technology during the Pandemic and to what extent they experienced Technostress, as well as the impact of Technostress on work-family conflicts and technology-induced health issues. A survey was conducted among 1172 primary school teachers, and the results revealed that teachers exhibited a moderate to a high level of Technostress during the Pandemic, with differences observed in gender, age, and headteacher duties. Furthermore, Technostress was positively correlated with work-family conflicts and technology-induced health issues. Technology use intensity was found to directly impact work-family conflicts and personal health and indirectly impact them via the agency effects of Technostress. School support moderated the indirect relationship between technology use intensity and work-family conflicts and health issues, with higher levels of school support leading to less apparent impacts of technology intensity on work-family conflicts and personal health via the agency effect of Technostress. These findings provide timely insights for post-pandemic teacher training and technology management and suggest the importance of school support in promoting sustainable educational development.